# Difference between revisions of "2014 USAMO Problems/Problem 2"

(→Alternative Solution) |
|||

Line 39: | Line 39: | ||

==Alternative Solution== | ==Alternative Solution== | ||

− | Given that the range of f consists entirely of integers, it is clear that the LHS must be an integer and <math>f(yf(y))</math> must also be an integer, therefore <math>\frac{f(x)^2}{x}</math> is an integer. If <math>x</math> divides <math>f(x)^2</math> for all integers <math>x \ne 0</math>, then <math>x</math> must be a factor of <math>f(x)</math>, therefore <math>f(0)=0</math>. Now, by setting <math>y=0</math> in the original equation, | + | Given that the range of f consists entirely of integers, it is clear that the LHS must be an integer and <math>f(yf(y))</math> must also be an integer, therefore <math>\frac{f(x)^2}{x}</math> is an integer. If <math>x</math> divides <math>f(x)^2</math> for all integers <math>x \ne 0</math>, then <math>x</math> must be a factor of <math>f(x)</math>, therefore <math>f(0)=0</math>. Now, by setting <math>y=0</math> in the original equation, this simplifies to <math>xf(-x)=\frac{f(x)^2}{x}</math>. Assuming <math>x \ne 0</math>, we have <math>x^2f(-x)=f(x)^2</math>. Substituting in <math>-x</math> for <math>x</math> gives us <math>x^2f(x)=f(-x)^2</math>. Substituting in <math>\frac{f(x)^2}{x^2}</math> in for <math>f(-x)</math> in the second equation gives us <math>x^2f(x)=\frac{f(x)^4}{x^4}</math>, so <math>x^6f(x)=f(x)^4</math>. In particular, if <math>f(x) \ne 0</math>, then we have <math>f(x)^3=x^6</math>, therefore <math>f(x)=0, x^2</math> for every <math>x</math>. Now, we just have to prove that if for some integer <math>t \ne 0</math>, if <math>f(t)=0</math>, then <math>f(x)=0</math> for all integers <math>x</math>. If we assume <math>f(y)=0</math> and <math>y \ne 0</math> in the original equation, this simplifies to <math>xf(-x)+y^2f(2x)=\frac{f(x)^2}{x}. However, since </math>x^2f(-x)=f(x)^2<math>, we can rewrite this equation as </math>\frac{f(x)^2}{x}+y^2f(2x)=\frac{f(x)^2}{x}<math>, </math>y^2f(2x)<math> must therefore be equivalent to </math>0<math>. Since, by our initial assumption, </math>y \ne 0<math>, this means that </math>f(2x)=0<math>, so, if for some integer </math>y \ne 0<math>, </math>f(y)=0<math>, then </math>f(x)=0<math> for all integers </math>x<math>. The contrapositive must also be true, i.e. If </math>f(x) \ne 0<math> for all integers </math>x<math>, then there is no integral value of </math>y \ne 0<math> such that </math>f(y)=0<math>, therefore </math>f(x)<math> must be equivalent for </math>x^2<math> for every integer </math>x<math>, including </math>0<math>, since </math>f(0)=0<math>. Thus, </math>f(x)=0, x^2$ are the only possible solutions. |

[[Category:Olympiad Algebra Problems]] | [[Category:Olympiad Algebra Problems]] | ||

[[Category:Functional Equation Problems]] | [[Category:Functional Equation Problems]] |

## Revision as of 12:04, 4 January 2019

## Problem

Let be the set of integers. Find all functions such that for all with .

## Solution

Note: This solution is kind of rough. I didn't want to put my 7-page solution all over again. It would be nice if someone could edit in the details of the expansions.

Lemma 1: . Proof: Assume the opposite for a contradiction. Plug in (because we assumed that ), . What you get eventually reduces to: which is a contradiction since the LHS is divisible by 2 but not 4.

Then plug in into the original equation and simplify by Lemma 1. We get: Then:

Therefore, must be 0 or .

Now either is for all or there exists such that . The first case gives a valid solution. In the second case, we let in the original equation and simplify to get: But we know that , so: Since is not 0, is 0 for all (including 0). Now either is 0 for all , or there exists some such that . Then must be odd. We can let in the original equation, and since is 0 for all , stuff cancels and we get: [b]for .[/b] Now, let and we get: Now, either both sides are 0 or both are equal to . If both are then: which simplifies to: Since and is odd, both cases are impossible, so we must have: Then we can let be anything except 0, and get is 0 for all except . Also since , we have , so is 0 for all except . So is 0 for all except . Since , . Squaring, and dividing by , . Since , , which is a contradiction for . However, if we plug in with and as an arbitrary large number with into the original equation, we get which is a clear contradiction, so our only solutions are and .

## Alternative Solution

Given that the range of f consists entirely of integers, it is clear that the LHS must be an integer and must also be an integer, therefore is an integer. If divides for all integers , then must be a factor of , therefore . Now, by setting in the original equation, this simplifies to . Assuming , we have . Substituting in for gives us . Substituting in in for in the second equation gives us , so . In particular, if , then we have , therefore for every . Now, we just have to prove that if for some integer , if , then for all integers . If we assume and in the original equation, this simplifies to x^2f(-x)=f(x)^2\frac{f(x)^2}{x}+y^2f(2x)=\frac{f(x)^2}{x}y^2f(2x)0y \ne 0f(2x)=0y \ne 0f(y)=0f(x)=0xf(x) \ne 0xy \ne 0f(y)=0f(x)x^2x0f(0)=0f(x)=0, x^2$ are the only possible solutions.